ASSESSMENT OF THE SOIL EROSION IN THE ÇOBANLAR BASIN, AFYONKARAHİSAR, TURKEY - Tevfik ERKAL (Fırat University, 2019)
Erosion is a natural process occurring very slowly that it is not easily understood by observation. It sometimes reaches big amount called natural hazard, especially in a country like Turkey having a young topography with steep slopes and high geomorphological amplitude. In this study Çobanlar sub-basin covers an area of 801 km² in the middle part of the 7340 km² Akarçay areic basin which is located in the Afyonkarahisar Province was investigated. Annually soil loss occurring in the Çobanlar basin was calculated by R(USLE) method using GIS and remote sensing techniques with the R (rainfall erosivity), LS (slope length and steepness), K (erodibility), C (cover and management) and P (conservation support and practice) factor layers and maps were prepared. So potential soil loss in the study area was determined using these layers and that it is 0-195 ton/ha/year. This value can be comparied to the studies carried out in other places of Turkey, points out that the Çobanlar sub-watershed is under the effect of moderate erosion risk. The reason of this result is based on erodibility of rocks such as easily eroded tuff, tuff-agglomerate and some metamorphic rocks. Beside this it was observed that erosion occurs severely around the scattering settlements in high topography in this sub-watershed.